Tiv economy - Bohannan, Paul.; Bohannan, Laura (London : Longmans, Green & Co, 1968)
This book is a result of 24 months period field work among the TIV between 1949 - 1953, it was financed by the Social science Research Council and the Government of Nigeria.
Includes index.
Include bibliographical references: p. 255-257.
ijb, 18/01/2019
Loans
Keywords: Tiv (African people); Economic history; Nigeria, Northern